Persistent Floating‐Body Effects in Fully Depleted Silicon‐on‐Insulator Transistors. Issue 9 (20th March 2020) - Park, Hyungjin; Colinge, Jean-Pierre; Cristoloveanu, Sorin; Bawedin, Maryline
Abstract : The floating‐body effects (FBEs) are widely documented in the history of silicon on‐insulator (SOI) transistors. The interest herein is threefold: 1) FBEs are revisited in the context of advanced fully depleted SOI with a thickness below 25 nm; 2) direct measurements of floating‐body potential enable in‐depth interpretation; and 3) additional evidence for the role of supercoupling is given. The typical consequences of FBEs (kink effect, parasitic bipolar transistor, transient and hysteresis in drain current, and metastable dip) are investigated and discussed. The critical roles of back‐gate biasing, body thickness, and frequency in the activation of FBEs are outlined. The signature of FBEs is still present in 12–25 nm films but disappears in sub‐10 nm‐thick transistors, due to the supercoupling effect. Abstract : The floating‐body effects are revisited in advanced fully depleted SOI transistors thinner than 25 nm. Direct measurement of floating‐body potential enables in‐depth interpretation of kink effect, hysteresis and transient current, parasitic bipolar transistor, and metastable dip. These effects are still present in 12–25 nm films but disappear in sub‐10 nm‐thick transistors, due to the supercoupling effect which is evidenced experimentally.